BALANCE SHEET CHANNEL OF MONETARY POLICY IN INDONESIAN MANUFACTURING FIRMS - Muhammad F. Alfarisy; Nopirin Nopirin; Iswardono S. Permono; Tri Widodo (Universitas Islam Indonesia, 2011)
This paper aims to test the hypothesis in a period of monetary tightening. Firms that face liquidity constraint and have limited access from external sources of funds will lower its investment. We use the panel data analysis of Indonesian manufacturing firms and financial variables, LIQ as the ratio between the sum of cash and marketable securities to total assets, and the change in cash flows as a proxy of firm’s liquidity constraint. The result provides some supports for the view that inventory in Indonesian manufacturing firms is sensitive toward cash flow during the monetary tightening period, especially for the firms that produce durable goods.Keywords: Monetary tightening, liquidity constraint, inventory investmentJEL classification numbers: G32, G38.